Síntese, caracterização de ferritas espinélio com propriedades magnéticas e absorvedoras de microondas - Silva, José Eves Mendes da (2013)
Were synthesized spinel-type ferrites with general formula Ni0,8Mg0.2-xMxFe2O4, where M represents the doping Mn, Co or Mn + Co simultaneously, x ranges for the values 0.02, 0.05 and 0.1. The value of x was divided by 2 in cases where M equals Mn and Co conjugates. We used the citrate precursor method and heat treatment to obtain the phases at 1100°C. The materials were characterized by XRD, TGA/ DTGA, SEM, MAV and reflectivity measurements by the method of waveguide. Powders to 350°C/3.5 h were crystalline and nanosized. According to the results this temperature all powders have a percentage of ferrite phase over 90%. The composition had the addition of Mn and Co simultaneously showed a higher percentage of secondary phase NiO, 5.8%. The TGA/DTGA curves indicate that this sample reached phase (s) crystalline (s) at lowest temperatures. The X-ray diffractograms of the samples calcined at 350°C and 1100°C were treated with the Rietveld refinament technique. The powders calcined at 1100 °C/3h in air show to be 100% except spinel phase composition with 0.02 doping. The micrographs show clusters of particles with sizes smaller than 1 μm in calcination temperature of 1100°C which agreed with the result of Rietveld refinement. In the compositions doped with Mn were higher values of magnetization (45.90 and 53.20 Am2/kg), which did not cause high microwave absorption. The theoretical calculation of magnetization (MT) was consistent with the results, considering that there was agreement between the increase of magnetization experimental and theoretical. It was observed that there was the interrelation of the final effect of absorption with the thickness of MARE, the composition of ferrimagnetic materials and in particular the specific values of frequency. The analysis shows that the reflectivity increases in the concentration of cobalt increased the frequency range and also for absorption 10.17 GHz and 84%, respectively. The best result of chemical homogeneity and the value of 2.96 x 10-2 tesla coercive field were crucial for high performance ferrite absorber with 0.1 cobalt. The Cobalt has high magnetocrystalline anisotropy, it is associated with an increased coercive field, Hc. Therefore, this property improves the results of reflectivity of spinel ferrites